Lyric audibility: In Public. Issue 5 (28th May 2018) - Roberts, Luke
ABSTRACT: This article offers a close reading of the poem 'In Public' by the American poet John Wieners (1934–2002), and explores how historical gay experience can be signalled poetically. Drawing on sociological accounts of public sex, I detail an erotics of silence and a concomitant erotics of listening. My commentary seeks to examine and extend the threshold of audibility in lyric poetry, finding meaning in absent words and in the marked suppression of sounds that carry social significance. With reference to the poet's notebooks, journals, and public readings, I position 'In Public' as a key moment in his literary development, written during a crucial phase of the struggle for gay liberation. I suggest that if we listen closely to 'In Public' we can hear a passionate lyric resistance to the language of psychiatry and the policing of same-sex desire.